Let x = Ruby's initial amount of money
5x = Sally's initial amount of money
5x - 80 = Sally's amount after Ruby spent $80
5x - 80 = (3/7)(5x)
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15x
7(5x - 80) = 15
Ruby had 5 times as much money as Sally. Ruby spent $80 and Sally had 3/7 as much as Ruby in the end. How much did Ruby have at first?
Show your work
1 answer